A man with dilated superficial abdominal veins. - Khalid Hamid Changal; Shoaib Altaf Sheikh; Adnan Raina (Babol University of Medical Sciences, 2016)
Background: The clinical presentation of non-Hodgkin lymphoma (NHL) varies tremendously depending upon the type of lymphoma and the areas of involvement. NHL can rarely present as an abdominal mass compressing the inferior vena cava. The clinical presentation due to obstruction of inferior vena cava has often been called the inferior vena cava syndrome (IVCS). It can present acutely or chronically. Case Presentation: A 35-year-old male presented with 3 months history of fever, anorexia, weight loss and abdominal discomfort. His abdominal examination showed dilated superficial veins with blood flowing rostrally. CECT abdomen revealed multiple enlarged some necrotic, retroperitoneal lymph nodes. The inferior vena cava was noted to be compressed by the lymph nodes. The lymph node biopsy revealed non- Hodgkin lymphoma, precursor B cell. Conclusion: An abdominal mass compressing the inferior vena cava is a rare but possible cause for appearance of dilated superficial abdominal veins and should be looked for.